Managerial accounting - Wild, John J. (McGraw-Hill Irwin, 2007)
Wild’s Managerial Accounting responds to the market’s request for a book with a balance between large and small business, and one that is contemporary yet succinct and assessable for today’s students. With numerous innovative features, the author focuses on “Three C’s”: Clear presentation of accounting concepts. Concise coverage to help students focus on important material, and Cutting-edge technology to engage students and improve their chances for success. The author provides a balance of small and large business examples, integration of new computerized learning tools, superior end-of-chapter materials, and highly engaging pedagogical learning structures. Technology tools such as Homework Manager provide students with further advantages as they learn and apply key accounting concepts and methods.